PAYMENTS FOR ENVIRONMENTAL SERVICES (PES): CHALLENGES AND OPPORTUNITIES FOR RURAL PRODUCERS AT SENHORA DE OLIVEIRA, MINAS GERAIS - Schettini, Bruno Leão Said; Pereira, Marcelo Gomes da Silva; Jacovine, Laércio Antônio Gonçalves; Rocha, Samuel José Silva Soares da; Villanova, Paulo Henrique; Comini, Indira Bifano (Floresta, 2020)
Payment for Environmental Services (PES) is an important tool for environmental conservation and is a relevant practice in many countries for the maintenance of forests. Thus, the objective of the present study was to evaluate challenges and opportunities of implementing a Payment for Environmental Services program in the municipality of Senhora de Oliveira, Minas Gerais. Socioeconomic and environmental diagnosis was performed using the Rapid Participatory Diagnosis technique. The total of 20 socioeconomic and environmental questionnaires were applied in the municipality, aiming to know in detail the local reality, raising potentialities and demands. The number of members of the 20 families that participated in the rural diagnosis was 72, of which 36 were men and 36 were women, with an average of 3.6 persons per family. Of the 20 rural properties that participated in the rural diagnosis, 35% have delimited RL areas and none of them has a management plan. The exploration of Legal Reserve occurs in 15% of the evaluated properties, being the production of firewood and cuttings the predominant activity. The average value of disposition receivable by rural producers was R 220.00 ha-1year-1, in which the producers who did not respond to this question were not considered. The municipality of Senhora de Oliveira, Minas Gerais has the necessary conditions to implement the PES, however the producers still do not receive any incentive to provide environmental services. If this process of PES is implemented, there will certainly be advances in environmental conservation and will bring social benefits throughout the region.